Pengaruh Proporsi Rumput Laut dan Sawo Mentega terhadap Serat Pangan, Aktivitas Antioksidan, Overrun, dan Sifat Organoleptik Sorbet - Astagina Sekar Sakti; Nanang Nasrulloh; A'immatul Fauziyah (Jurnal Pangan dan Gizi, 2022)
Lack of fiber and antioxidants can increase the risk of obesity which lead to oxidative stress. Eucheuma cottonii seaweed contains dietary fiber which provide anti-obesity effects. Beside dietary fiber, antioxidant is also needed to prevent oxidative stress in obesity. Canistel fruit (Pouteria campechiana) contains antioxidants such as vitamin C, beta carotene and polyphenols. The purpose of this study was to determine the effect of the proportion of seaweed and canistel on the content of dietary fiber, antioxidant activity, physical properties, and organoleptic properties of sorbet. This research method used a one-factor completely randomized design (CRD) with two repetitions. These factors are the proportion of seaweed and canistel, namely F1 (20%:80%), F2 (30%:70%), and F3 (40%:60%). The ANOVA test results showed that the proportion of seaweed and canistel had a significant effect (p< 0.05) on the dietary fiber and overrun, while the antioxidant activity and organoleptic properties of sorbet had no significant effect (p >0.05). The selected formula by using Exponential Comparison Method (ECM) results the F1 formula with the proportion of 20%:80%. The selected formula products contained 5.19% dietary fiber, 48% w / v antioxidant activity, and 34.32% overrun.